The role of mentorship in the management of educational institutions (MMIT Proceedings, 2025)
In this article, the pedagogical skills and significance of teachers in the management of educational institutions, the current attention of state policy to the personality of the teacher, the professional skills of teachers in increasing the effectiveness of management, the study and analysis of foreign experience, the influence of pedagogical skills in management, methods and significance of improving pedagogical skills are analyzed in depth. The teacher's management culture, image, and style. Factors influencing the formation of relationships in the educational process, the creation of an educational and upbringing environment, and the management of organizational processes. The features of the teacher's activity in managing the educational system and educational institution, leadership abilities, and its organization are theoretically highlighted